2022
DOI: 10.1590/1678-4162-12743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal environment on dairy cattle under a grazing system in the Western Amazon, Brazil

Abstract: This study aimed to evaluate the thermal conditions to which animals are exposed and their effect on the comfort/discomfort of dairy herds in a grazing system in the municipality of Sena Madureira, Acre State, Brazil. Eight farms and a total of 113 lactating crossbred cows were evaluated. Dry-bulb temperature (DBT, °C), relative humidity (RH, %), black globe temperature (BGT, °C), and wind speed (v, km h−1) were measured in January, February, and March (rainy season) to calculate temperature-humidity index (TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…In an experiment carried out in the municipality of Sena Madureira-Acre, from January to March 2020, it was observed that the THI values were ≥72, and a similar result was also evidenced in this study in Rio Branco (Acre), which indicated a minimum THI of 72 in January (45). According to Soares et al ( 46), the high rates of THI favor the stimulus of thermal stress and, consequently, influence the reduction of milk production, reproduction, and low animal welfare performance in dairy cows (15, 31).…”
Section: Discussionsupporting
confidence: 87%
“…In an experiment carried out in the municipality of Sena Madureira-Acre, from January to March 2020, it was observed that the THI values were ≥72, and a similar result was also evidenced in this study in Rio Branco (Acre), which indicated a minimum THI of 72 in January (45). According to Soares et al ( 46), the high rates of THI favor the stimulus of thermal stress and, consequently, influence the reduction of milk production, reproduction, and low animal welfare performance in dairy cows (15, 31).…”
Section: Discussionsupporting
confidence: 87%